Promotion of prostitution services on social media - Juditha, Christiany; Eni Maryani,; Abdullah, Aceng; Rahmi Setiawati, (Penerbit Universiti Kebangsaan Malaysia, 2022)
If in the past, promotion of sexual services was done face to face – on the streets or brothels – but now it has turned to social media. Data shows that online prostitution continues to increase because it can be accessed easily on social media. Social media, with its more open communication, is considered adequate for the promotion of commercial sex services. The purpose of this study is to get an overview of the interaction and communication with regards to online promotion of prostitutions on social media. Netnography is the research method chosen. The results of the study concluded that in the interaction regarding prostitution on social media and communication between fellow perpetrators is very open and vulgar. Commercial sex workers and pimps are the main promoters of the services offered. The message conveyed includes the services offered, ways of payment, and rules of the game accompanied by terms and conditions that are commonly used among actors. The use of the hashtag (#) by service providers helps facilitate the promotion and search for customers. In addition to the timelines used by actors, social media commentary, and the direct message (DM) feature are also used for communication purposes. Furthermore, if there has been an agreement between the actors, an extension of the private communication is continued through instant messaging such as talking about time, location of the service, payment and sharing of testimonials from previous customers.